Improving food security, nutrition, incomes, natural resource base, and gender equity for better livelihoods of smallholders in sub-Saharan Africa - Seven Years of Impact: 2015–2021. Summary Report submitted to SDC October 2022 - Pan-Africa Bean Research Alliance (2022)
The Eastern and Southern Africa (ESA) Division of SDC has supported PABRA in its 25 years over various project phases with core contributions to PABRA covering 21 countries of the two networks, Eastern and Central Africa Bean Research Network (ECABREN) and Southern Africa Bean Research Network (SABRN1). The last phase covered from 2015 to 2021, when the ESA Division supported PABRA to implement the “Improving food security, nutrition, incomes, natural resource base, and gender equity for better livelihoods of smallholder households in sub-Saharan Africa” project worth US$13.7 million. This project applied the PABRA model with a special focus on Burundi and Zimbabwe.